2017
DOI: 10.1590/0103-8478cr20160150
|View full text |Cite
|
Sign up to set email alerts
|

Brachiaria physiological parameters in agroforestry systems

Abstract: This study aimed to assess the effects of Eucalyptus and maize shading on characteristics related to water use by Brachiaria in agroforestry systems. Treatments were arranged in a split-split-plot design, with plots consisting of different spacing between Eucalyptus plants (12.0×2.0m and 12.0×4.0m), split-plots of different distances between Brachiaria and Eucalyptus (6.0, 4.0, and 2.0m), and split-split-plots of Brachiaria sowing sites (maize row and inter-row). One treatment with Brachiaria under full sunlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
1
6
0
3
Order By: Relevance
“…Silvopastoral systems have been proposed as a means of intensifying beef production systems by associating trees, planted pastures, and animals (Paciullo et al, 2017). Tropical forage grasses, however, are generally more efficient and better adapted to full sun (Santos et al, 2017) and the impact of pasture shading in an SPS needs to be quantified and rationalized.…”
mentioning
confidence: 99%
“…Silvopastoral systems have been proposed as a means of intensifying beef production systems by associating trees, planted pastures, and animals (Paciullo et al, 2017). Tropical forage grasses, however, are generally more efficient and better adapted to full sun (Santos et al, 2017) and the impact of pasture shading in an SPS needs to be quantified and rationalized.…”
mentioning
confidence: 99%
“…As espécies de brachiaria em diferentes arranjos de sistema agrossilvipastoril prejudicou o desenvolvimento do eucalipto em fileiras com milho para todas as variáveis ecofisiológicas estudadas por Santos et al (2017). No estudo, a espécie B. decumbens em competição com as mudas de P. dubium apresentou os maiores incrementos em MSPA, MSR e MST, se diferenciando estaticamente apenas da B. pilosa nas variáveis mencionadas e da B. brizantha para a MSR e MST (Tabela 4).…”
Section: Resultsunclassified
“…Our results showed that the sampling point near the double rows of eucalyptus contributed to variations in the physiological parameters of forage grass in relation to the alley (Figure 3). Santos et al (2017) also found that shading contributed to the reduction in E and Gs for soybean plants within an agrosilvopastoral system, identifying that lower spacing from the eucalyptus affected the physiological parameters. The authors highlighted that reduction in light intensity and the high density of forage plants in addition to the greater proximity to eucalyptus trees could limit the photosynthetic rate, especially for C4 plants.…”
Section: Physiological Parameters Of Marandu Palisadegrass Within the Silvopastoral Systemmentioning
confidence: 85%